Improving and promoting VET : BIBB and its global network of partners - Kissling, Hans-Joachim [Verfasser] (Bundesinstitut für Berufsbildung, 2013)
Pursuant to the Vocational Training Act (BBiG), the Federal Institute for Vocational Education and Training (BIBB) engages in international cooperation in vocational education and training within the scope of the Federal Government's education policy. Accordingly, BIBB is active at the European and global level. Worldwide, BIBB has cooperation agreements in place with more than 30 vocational education and training institutes. The objects of these agreements are the regular exchange of information and cooperation in specific projects. The present BIBB publication on the occasion of WorldSkills Leipzig 2013 is intended not just to document that exchange among partners but to deepen it. On the one hand, it is meant to document the national responsibilities and international cooperation projects of the BIBB. On the other hand, it is a comprehensive presentation of the leading vocational education and training institutes all over the world, of their tasks and objectives, their research and development activities and their cooperation projects within international networks. (BIBB)
Keywords: I 1 Internationale Berufsbildung; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Bundesinstitut für Berufsbildung; Internationale Zusammenarbeit; Berufsbildungsforschung